2018
DOI: 10.3389/fnins.2018.00655
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Mapping of Cerebral Propagation in Amyotrophic Lateral Sclerosis

Abstract: Neuropathological studies revealed the propagation of amyotrophic lateral sclerosis (ALS) in a sequence of four separate disease-related regional patterns. Diffusion tensor imaging (DTI)-based analysis was established for the individual mapping of sequential disease spreading in ALS as the in vivo transfer to neuroimaging. The aim of this review is to summarize cross-sectional and longitudinal results of these technical approaches in ALS as an in vivo tool to image ALS propagation stages. This concept was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…This system plays an important role in movement regulation and modulates higher cognitive functions ( Palesi et al, 2017 ; Wagner and Luo, 2020 ). Based on a multicenter DTI study, corticopontine tract (CPT) FA decreases have been related to stage 2 of a lately suggested pathological staging system ( Kassubek et al, 2014 ; Müller and Kassubek, 2018 ). Moreover, a DTI study has shown that disruption of white matter integrity of the cortico-ponto-cerebellar system in ALS patients was associated with the pseudobulbar syndrome, ( Floeter et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This system plays an important role in movement regulation and modulates higher cognitive functions ( Palesi et al, 2017 ; Wagner and Luo, 2020 ). Based on a multicenter DTI study, corticopontine tract (CPT) FA decreases have been related to stage 2 of a lately suggested pathological staging system ( Kassubek et al, 2014 ; Müller and Kassubek, 2018 ). Moreover, a DTI study has shown that disruption of white matter integrity of the cortico-ponto-cerebellar system in ALS patients was associated with the pseudobulbar syndrome, ( Floeter et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…DTI metrics maps (FA, axial diffusivity—AxD, radial diffusivity—RD, mean diffusivity—MD) are calculated from these stereotaxically normalized data sets and are in a following step smoothed with a Gaussian filter with a size of about two to three times the recording voxel size, that way providing a good balance between sensitivity and specificity. The axonal damage and myelin degradation is mirrored by DTI metrics; differences at the group level to assess microstructural alterations by statistical analysis of DTI metrics can be performed by various approaches (Müller and Kassubek, 2018 ): (1) unbiased voxelwise comparison by whole brain-based spatial statistics (WBSS) (Müller et al, 2012b ) or tractwise comparison by tract-based spatial statistics (TBSS) (Smith et al, 2006 ) or (2) hypothesis-guided tract-based quantification by analyzing DTI metrics in tract systems by TOI-based tractwise FA statistics (TFAS) (Müller et al, 2007 ) ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, FTD patients occasionally develop motor neuron disease, and for this reason, ALS and FTD have been suggested to be at the edges of the same disease spectrum (Couratier et al, 2017). These observations have been possible thanks to the combination of clues derived from human post‐mortem material (Braak & Braak, 1991; Strong et al, 2005; Kalaitzakis et al, 2008), longitudinal neuroimaging of living patients (Ewers et al, 2008; Seeley et al, 2009; Brettschneider et al, 2015; Müller & Kassubek, 2018; Young et al, 2020), and clinical monitoring (Perlmutter, 2009; Turner et al, 2010; Agüera‐Ortiz et al, 2010; Fang et al, 2017). Additionally, the development of in vitro and in vivo disease models has helped to elucidate, at least in part, the molecular basis of disease pathogenesis (Luk et al, 2012; Ruiz‐Riquelme et al, 2018; Kim et al, 2019; McAlary et al, 2019).…”
Section: The Progressive Nature Of Neurodegenerative Diseasesmentioning
confidence: 99%